Biomechanical analysis of upper extremity of tennis flat services - Tsai, C. L.; Lin, D. C.; Huang, C.; Cheng, C. C. (2000)
The purpose of this study is to analyze the net joint forces, moments and powers on the upper extremities of the elite players during the flat service movement. In this study, we are interested in analyzing from the phase of the period before and after the point of making contact with the ball. Four elite collegiate players in Taiwan were served as subjects. The upper extremity of the subject was separated into three segments, upper arm, forearm and racket (with fist included). The body segment parameters of each subject were calculated by a mathematical model of truncated elliptical cone and calibrate by reaction board and water displacement methods. A Kodak Ekta-Pro 1000 high-speed video camera (500Hz) was used to record the 2D kinematics data. The inverse dynamics solution was employed calculate the forces, moments and powers of the upper segment joints. From these data, we can understand the power balance within the segments. The results were concluded as follows: By analyzing the acceleration stage of the tennis serve, the net joint forces, net joint moments and power simultaneously attained peak values at the time of contact. The wrist joint has the greatest angular velocity, angular acceleration and joint power during the contact phase. From the analysis of the motion of the upper extremities, it is realized that regular training on the elbow flexor will reduce likelihood of injury due to stress the flexor through eccentric contraction during acceleration phase. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)